Impact of a Six-Week Prehabilitation With Blood-Flow Restriction Training on Pre- and Postoperative Skeletal Muscle Mass and Strength in Patients Receiving Primary Total Knee Arthroplasty - Franz, Alexander; Ji, Sanghyeon; Bittersohl, Bernd; Zilkens, Christoph; Behringer, Michael (Frontiers in Physiology, 2022)
Total Knee Arthroplasty (TKA) is one of the most successful interventions in gonarthrosis, however the operation is leading to muscle atrophy and long-term muscular deficits. To enhance rehabilitation after TKA, exercise programs try to improve muscle function preoperatively, called prehabilitation. Blood-Flow-Restriction (BFR) is a training method which is characterized by using tourniquets to reduce venous flow during the exercise to increase metabolic stress. The present study aimed to evaluate the effects of a six-week prehabilitation with BFR on pre- and postoperative muscle mass, strength, and quality of life (QoL). 30 patients with end-stage gonarthrosis participated in this study. Patients were randomized into one of three groups: 1) Control-Group (CON): Standard clinical approach without prehabilitation. 2) Active-Control-Group (AC): Participation in a prehabilitation with sham-BFR. 3) BFR-Group (BFR): Participation in a prehabilitation with additional BFR. The prehabilitation protocol consist of a cycling-ergometer-based training performed twice per week over six weeks. During exercise, BFR was applied periodically three times per leg with a pressure of 40% of the individual-limb-occlusion-pressure. Measurement time points were six- (baseline), three-weeks and five-days before the surgery (Pre-OP), as well as three- and six-months postoperatively. Outcome parameters were muscular strength of the thigh muscles, thigh circumference as well as QoL and functional activity. Prehabilitation was able to increase muscle strength and QoL in gonarthrosis-affected patients. In comparison, BFR was able to increase muscle strength and mass significantly superior to AC over the six-week prehabilitation phase (p<0.001). Early Rehabilitation illustrated a characteristic decline in muscle strength with inverse improved pain perception three-months post-TKA (p<0.05). However, BFR as the exclusive group did not drop below baseline levels (p>0.8). After six months, all groups documented enhancements in muscle strength and QoL (p<0.01). In comparison, BFR group revealed significant better outcomes, reporting improved results after six-months compared to Pre-OP values. The present findings show that BFR-prehabilitation induce significant improvements in muscle function and QoL before TKA surgery. In addition, the supporting effect of prehabilitation on postoperative regeneration and QoL should be highlighted, illustrating prolonged beneficial effects of BFR on muscular and functional performance in a “better in, better out”-manner.